Influence of Ease of use, Usefulness and Application Feature toward Repurchase Intention on E-Ticketing by TIX ID Application in Medan City - Bella Viona; Callista Lieviera; Eleanor Gwyneth; Eliza Gany; Ellen Irana; Khalizs A. Siregar (MultiTech Publisher, 2019)
The study examines the factors influencing repurchase intentions in the context of E-Ticketing, focusing on the TIX ID application in Medan City. The factors investigated are ease of use, usefulness, and application features. Ease of use refers to the user-friendliness of the application, while usefulness relates to the perceived benefits users derive from it. Application features encompass the functionalities and capabilities offered by the app. The research aims to understand how these factors collectively impact users' likelihood to repurchase through the TIX ID application. The findings will shed light on the significance of these elements in shaping consumer behavior within the E-Ticketing realm, aiding businesses in enhancing their services and strategies for greater customer retention and repurchase rates